From Authenticity to Measurable Impact: IFAS–EFAS SWOT and SMART Digital Marketing Strategy for Pasar Bahulak Cultural Tourism - Rahmawati, Rahmawati; Nasution, Mohamad Nur Afriliandi; Majid, Asmarani; Isma, Andika (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
Community-based cultural destinations often possess strong authenticity but struggle to translate it into consistent digital communication and measurable local economic gains. This study assesses the current marketing approach of Pasar Bahulak and formulates more effective, sustainability-aligned promotional recommendations. Using a descriptive qualitative design, evidence from observation and documentation was organized thematically and integrated into a SWOT framework, operationalized via IFAS (internal factors) and EFAS (external factors) to derive SO/WO/ST/WT alternatives and a SMART implementation plan. The analysis produced an IFAS score of 3.33 and an EFAS score of 3.30, positioning the destination in Quadrant I and indicating an aggressive-growth (SO) orientation. Accordingly, the recommended strategy prioritizes leveraging distinctive cultural experience attributes, active social media presence, and community support to capture rising demand for local-experience tourism through more systematic digital campaigning, creator collaborations, and improved informational clarity for trip planning, while mitigating competitive and platform-volatility risks. To operationalize execution, a SMART objective is proposed that focuses on conversion quality rather than volume by increasing average on-site spending per visit from an early baseline of approximately IDR 19,091 to IDR 22,000–25,000 within a short evaluation window, monitored at each market day. These findings imply that combining IFAS–EFAS quadrant diagnosis with SMART targets can help cultural destinations move from visibility to measurable community economic impact while keeping promotional efforts aligned with alternative-tourism sustainability principles.